Square Biphasic Pulse Deep Brain Stimulation for Parkinson’s Disease: The BiP-PD Study - De Jesus, Sol; Okun, Michael S.; Foote, Kelly D.; Martinez-Ramirez, Daniel; Roper, Jaimie A.; Hass, Chris J.; Shahgholi, Leili; Akbar, Umer; Wagle Shukla, Aparna; Raike, Robert S.; Almeida, Leonardo (Frontiers in Human Neuroscience, 2019)
Background Conventional Parkinson’s disease (PD) deep brain stimulation (DBS) utilizes a pulse with an active phase and a passive charge-balancing phase. A pulse-shaping strategy that eliminates the passive phase may be a promising approach to addressing movement disorders. Objectives The current study assessed the safety and tolerability of square biphasic pulse shaping (sqBIP) DBS for use in PD. Methods This small pilot safety and tolerability study compared sqBiP versus conventional DBS. Nine were enrolled. The safety and tolerability were assessed over a 3-h period on sqBiP. Friedman’s test compared blinded assessments at baseline, washout, and 30 min, 1 h, 2 h, and 3 h post sqBIP. Results Biphasic pulses were safe and well tolerated by all participants. SqBiP performed as well as conventional DBS without significant differences in motor scores nor accelerometer or gait measures. Conclusion Biphasic pulses were well-tolerated and provided similar benefit to conventional DBS. Further studies should address effectiveness of sqBIP in select PD patients.